Population dynamics of mistletoes species on Cassia fistula in Purwodadi Botanic Garden, Indonesia - Solikin Solikin (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Solikin. 2021. Population dynamics of mistletoes species on Cassia fistula L. in Purwodadi Botanic Garden, Indonesia. Biodiversitas 22: 1612-1620. Several species of mistletoe are parasitizing and infesting cultivated plants in Purwodadi Botanic Garden, Pasuruan, East Java i.e. Dendrophthoe pentandra (L.) Miq., Macrosolen tetragonus (Blume) Miq., Scurrula atropurpurea (Blume) Danser, Viscum articulatum Burm.f., and Viscum ovalifolium Wall. ex DC. The population of the mistletoes is dynamics affected by genetic and environment. The study aimed to investigate the population dynamics of mistletoe species on Cassia fistula L. in Purwodadi Botanic Garden, Indonesia. Data collection was conducted by direct observation in the garden on the mistletoe species, parasite density, and host prevalence in four block locations and 28 trees of C. fistula. Data were analyzed by two-way ANOVA and tested by Least Significantly Difference (LSD) if there was a significant difference in blocks and year. The results showed two species of mistletoe found on C. fistula, i.e. D. pentandra and V. articulatum. Parasitic density was significant different and infested host prevalence also different in blocks and years. The highest parasite density per host plant was reached in block III.D in 2015,i.e. 7.00±2.95 and 2.28±0.85 individuals per plant for D. pentandra and V. articulatum, respectively. The highest infested host prevalence of 100.00 was reached in block III.D in 2015 and XVI.A since 2012.